Isolation of mutations affecting neural circuitry required for grooming behavior in Drosophila melanogaster. - Phillis, R.W.; Bramlage, A.T.; Wotus, C.; Whittaker, A.; Gramates, L.S.; Seppala, D.; Farahanchi, F.; Caruccio, P.; Murphey, R.K. (Genetics, 1993)
We have developed a screen for the isolation of mutations that produce neural defects in adult Drosophila melanogaster. In this screen, we identify mutants as flies unable to remove a light coating of applied dust in a 2-hr period. We have recovered and characterized six mutations and have found that they produce coordination defects and some have reduced levels of reflex responsiveness to the stimulation of single tactile sensory bristles. The grooming defects produced by all six of the mutations are recessive, and each of the mutations has been genetically mapped. We have also used our assay to test the grooming ability of stocks containing mutations that produce known neural defects.